Exploring the causes and consequences of maternal metabolic maladaptations during pregnancy: Lessons from animal models. (1st September 2020) - Sferruzzi-Perri, Amanda N.; Lopez-Tello, Jorge; Napso, Tina; Yong, Hannah E.J.
Abstract: Pregnancy is a remarkable physiological state, during which the metabolic system of the mother adapts to ensure that nutrients are made available for transfer to the fetus for growth and development. Adaptations of maternal metabolism during pregnancy are influenced by the metabolic and nutritional status of the mother and the production of endocrine factors by the placenta that exert metabolic effects. Insufficient or inappropriate adaptations in maternal metabolism during pregnancy may lead to pregnancy complications with important short- and long-term effects for both the health of the child and mother. This is very evident in gestational diabetes, which is marked by greater glucose intolerance and insulin resistance above that expected of a normal pregnancy. Gestational diabetes is associated with increased fetal weight and/or increased adiposity, higher instrumented delivery rates and greater risks for both mother and child of developing type 2 diabetes in the long-term. However, despite the negative health impacts of such metabolic imbalances during pregnancy, the precise mechanisms responsible for orchestrating these changes remain largely unknown. The present review describes the dynamic pregnancy-specific changes that occur in the metabolic system of the mother during pregnancy. It also discusses findings using surgical, pharmacological, genetic and dietary methods in experimental animals that highlight the role of pathways in maternal tissues that lead to metabolic dysfunction, with a particular focus on gestational diabetes. Finally, it summarises the work largely employing gene targeting and hormone administration in rodents that have illuminated the involvement of placental endocrine function in driving maternal metabolic adaptations. While current animal models may not fully replicate what is observed in humans, these have been instrumental in showing that there is a dynamic interplay between changes in maternal metabolic physiology and the placental production of endocrine factors that govern the availability of nutrients to the growing fetus. However, more work is required to specifically identify the placenta-driven changes in maternal metabolic physiology that ensure the appropriate level of insulin production and action during pregnancy. In doing so, these studies may pave the way to understanding the development of pregnancy complications like gestational diabetes, as well as further our understanding of type-2 diabetes and the control of metabolic physiology more broadly.